Application Progress of Traditional Chinese Medicine as an Adjuvant Therapy for Cardiovascular and Cerebrovascular Diseases - Ding, Shuxiu; Li, Ruoqi; Sun, Yuxin (Transactions on Materials, Biotechnology and Life Sciences, 2024)
At present, CVDs are a crucial problem that has puzzled many researchers for a long period. It has a high fatality rate because it will cause many complications and adverse effects on metabolism. Many side effects of pharmaceutical drugs are very serious because the majority of medicine that treat CVDs are western medicines. Pathogenic factors could not be inhibited effectively and the appropriate target spot was not discovered. However, more and more new technologies and drugs have developed and improved in treating this disease. The combination of TCM and WM has profound prospects. Especially in the clinical treatments of CVDs, TCMs play a role as adjunctive drugs by promoting blood circulation and removing blood stasis. And it can be used for reducing the toxic and side effects of chemical medicines. This integrated method not only maintains the traditional theory and drugs such as herbal, animal and mineral materials but also improves therapeutic effects by combining WM and using advanced devices, artificial intelligence and Western dosage forms. These integrative methods can effectively improve the therapeutic effects and reduce the frequency of adverse effects. Scientists made great progress and achievements in this field. However, the specific mechanism of action of the compounds still needs to be explained deeply.